Analysis of Stakeholder Collaboration in Local Rice Seed Governance in West Sumatra: Fuzzy Delphi Approach to Improve Food Security and Sustainable Agriculture - Masruri, -; Hadiguna, Rika Ampuh; Suliansyah, Irfan; Henmaidi, - (JOIV : International Journal on Informatics Visualization, 2025)
Local rice seeds are crucial to Indonesia's food security and agricultural sustainability, especially in West Sumatra. Seed management has yet to achieve seed independence, hindering the development of breeders and seed users. Overcoming this requires collaboration between stakeholders because locals can take collective responsibility and build trust in the Government through collaborative seed governance. This study introduces the concept of assessing the level of collaboration between stakeholders to analyze the stages of cooperation currently occurring in the governance of local rice seeds in West Sumatra. This study employs a mixed-methods approach, combining quantitative and qualitative methods. The study involved interviews with experts and a literature review, identifying 14 indicators influencing collaboration in seed governance. After validation by 5 (five) Experts, 13 (thirteen) indicators were obtained for further analysis using the Fuzzy Delphi, which was applied through a questionnaire distributed to 30 (thirty) informants representing stakeholders in five Regencies/Cities selected purposively in West Sumatra Province. The results were analyzed using a Likert scale and converted to fuzzy logic. These indicators are categorized into 5 (five) characteristics of collaboration. This study found that the level of collaboration between stakeholders is at the "cooperation" stage, which shows a significant lack of effectiveness in the interaction between stakeholders. This study offers valuable insights for stakeholders to enhance the collaborative process of local rice seed management, thereby achieving food security and sustainable agriculture.